PENGARUH PANJANG KAWAT KONSTAN DAN NIKROM TERHADAP BESAR RESISTENSI KONVERSI - Rustiani, Eka Astria; Nur Rosyidah, Anis; Nugraha, Rahmat Ramdan; Anugrah, Dea Rizky; Gunawan, Anisa Mutmainah; Putri, Fuzi Nurfauzia Sugiharto; Malik, Adam (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
This article discusses the importance of electricity in everyday life and its role in the development of modern technology. This research focuses on conducting resistance analysis using constant wire and nichrome wire. The research method used is a quantitative method using experimental methods. Data is measured using a wire to conduct electricity from the power supply or voltage. The results showed a relationship between the wire's length and the conductor's resistance. The longer the wire, the more excellent the opposition to its conduction. In addition, the type of wire also affects the resistance of the conductor, with nichrome wire having a more excellent resistance than constant wire. In conclusion, the value of the resistance of the conductor is proportional to the length of the wire and the type of wire used. However, it should be kept in mind that these conclusions only apply to the experimental situations conducted in this study.